Mental and Behavioral Problems in Medical Students of a Health Science Institute in Eastern Nepal - Shakya, Dhana Ratna; Shyangwa, Pramod Mohan; Shakya, Rabi; Agrawal, Chandra Shekar (Journal of Psychiatrists' Association of Nepal, 2022)
Introduction: Literature shows a high prevalence of mental disorders among medical students. Psychiatric morbidity data help enhance all levels of management. We have limited data about 'mental and behavioural problems' in medical students. Objective: To see and sort out psychiatric problems among medical students of BP Koirala Institute of Health Sciences (BPKIHS), Nepal. Methodology: It is an institute based prevalence study. Twenty percentages of all medical students of all programs (1125) of academic year of 2008/9 were (systematic) randomly selected. After informed written consent, the subjects were enrolled. A semi-structured proforma was used to record socio-demographic and clinical profiles. The 'Structured clinical interview for DSM-IV Axis I disorders' (SCID-I) was used to diagnose major psychiatric disorders. Result: Out of the total sample students, 219 students were enrolled. Among the enrolled subjects, life time diagnosis of psychiatric problem (till the time of the study) was about 55%. At the time of the study, approximately 30% had psychiatric problem. During BPKIHS stay inclusive of current problem, slightly more than 40% had mental problems. The most common diagnosis was adjustment disorder. Conclusion: A great proportion of medical students suffer from mental and behavioural problems.